Security and Data Storage Aspect in Cloud Computing - Deshpande, Prachi S.; Sharma, Subhash C.; Peddoju, Sateesh K. (Studies in Big Data, 2019)
This book analyses the various security threats in cloud computing. A host-based IDS (HIDS) using signature verification is developed and implemented for the concerned security issues. Further, owing to the vulnerability of distributed denial of service (DDoS) attacks in cloud computing, a network based IDS (NIDS) is developed and implemented against such attacks. The performance of these IDS is verified in the Cloud scenario as well against the standard data set. Finally, a simple data storage and security model is developed and implemented for the Cloud computing scenario. The contents of this book will be of interest to researchers and professionals alike.